2013
DOI: 10.1021/am302912v
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Assistance in Improvement of Photocatalytic Hydrogen Production with the Porphyrin Noncovalently Functionalized Graphene Nanocomposite

Abstract: In this paper, a 5,10,15,20-tetrakis(4-(hydroxyl)phenyl) porphyrin (TPPH) noncovalently functionalized reduced graphene oxide (RGO) nanohybrid has been facilely synthesized by immobilizing TPPH on RGO nanosheets. This nanohybrid was characterized by atomic force microscopy (AFM), transmission electron microscopy (TEM), and UV-vis spectra, which demonstrated that the TPPH molecule was attached on the surface of the graphene nanosheet. The results of fluorescence quenching and photocurrent enhancement of TPPH-RG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 56 publications
7
130
2
Order By: Relevance
“…It can be seen that the intensity ratio of FGO-PN (I D /I G = 1.44) increases with respect to the GO ratio (I D /I G = 1.40), which is consistent with the introduction of defects on the FGO surface. These changes may be due to the π-π interaction between the FGO and PN, which is in agreement with results presented recently by other researchers [28].…”
Section: Resonant Raman Scatteringsupporting
confidence: 93%
See 1 more Smart Citation
“…It can be seen that the intensity ratio of FGO-PN (I D /I G = 1.44) increases with respect to the GO ratio (I D /I G = 1.40), which is consistent with the introduction of defects on the FGO surface. These changes may be due to the π-π interaction between the FGO and PN, which is in agreement with results presented recently by other researchers [28].…”
Section: Resonant Raman Scatteringsupporting
confidence: 93%
“…In FGO-PN we find that the relative intensities of these bands change significantly. Moreover, the absence of the band at 1408 cm -1 and the shift of the N-H band indicate a strong interaction between FGO and PN [28], confirming our results obtained by resonant Raman spectroscopy and steady-state photoluminescence. …”
Section: Ft-ir Measurementssupporting
confidence: 90%
“…From the Raman spectrum of GeS 2 -rGO, it can be found that there exist two obvious Raman peaks at 1320 cm -1 and 1599 cm -1 . These peaks ought to correspond to the D band and G band of reduced graphene oxide (RGO), respectively [4]. In addition, compared with GO, the intensity ratio of the D band to G band (I D /I G ) of GeS 2 -rGO increases from 0.93 to 1.86 after solvothermal treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, several groups found a good application prospect of graphene in dyesensitized system, where graphene as an electron acceptor and transporter can efficiently promote the electron transfer between the photosensitizer and the catalysts, because of the well-aligned energy levels between the different components [77][78][79]. Especially, Lu group has carried out much impressive work in this area.…”
Section: Graphene-based Mixed-colloid Photocatalytic Systemsmentioning
confidence: 99%